The Mughal Empire at War Babur, Akhbar and the Indian military revolution, 1500-1605 - De la Garza, Andrew 1968- (Asian states and empires, 2016)
The book traces the development of the Mughal Empire chronologically, examines weapons and technology, tactics and operations, organization, recruitment and training, and logistics and non-combat operations, and concludes by assessing the overall achievements of the Mughal Empire, comparing it to its Western counterparts, and analyzing the reasons for its decline